Integrin-Linked Kinase: A Multi-functional Regulator Modulating Extracellular Pressure-Stimulated Cancer Cell Adhesion through Focal Adhesion Kinase and AKT - Shouye Wang; Marc D. Basson (Cellular Oncology)
Cell adhesion is important in cancer metastasis. Malignant cells in cancer patients may be exposed to physical forces such as extracellular pressure and shear, that stimulate their adhesion to matrix proteins, endothelium and surgical wounds. Pressure induces phosphorylation of AKT and focal adhesion kinase (FAK), which are required for pressure-stimulated cancer cell adhesion, but what mediates this effect is unknown. ILK may influence cell adhesion and FAK and AKT phosphorylation in other settings. We therefore hypothesized that ILK might also regulate pressure-stimulated cancer cell adhesion through AKT and FAK phosphorylation. Silencing ILK by siRNA reduced basal cancer cell adhesion and prevented the stimulation of adhesion by pressure. ILK mediated pressure-stimulated adhesion through specifically regulating phosphorylation of AKT at Ser473 and FAK at Tyr397 and 576 as well as ILK association with FAK and AKT. The siRNA-mediated loss of function of ILK in regulating increase in adhesion by pressure was not rescued by overexpression of α-parvin, an important ILK binding partner, although pressure promoted ILK–α-parvin association and translocated both ILK and α-parvin from cytosol to membrane/cytoskeleton. ILK may be a key mediator of mechanotransduced signals in cancer cells and an important therapeutic target to inhibit metastatic cancer cell adhesion.